Time course of sutural width during the physiological growth from birth to adulthood: CT quantitative and qualitative evaluations of sutural arches. - Calandrelli, Rosalinda; Pilato, Fabio; D'Apolito, Gabriella; Tuzza, Laura; Colosimo, Cesare (Neuroradiology, 2023)
Purpose: We performed a retrospective qualitative and quantitative evaluation of the sutural changes during the physiological growth to define the age-related ossification stages of major and minor skull sutures or synchondroses. Methods: A total of 390 healthy subjects, examined for cranio-facial trauma and whose CT scans turned out to be normal, were clustered into homogenous age-matched groups ranged from birth to 90 years. High-resolution CT was used to assess the degree of sutural closure according to a 3-grade scoring system, the sutural pattern, the width, and the density of the gap calculated as the average of two or three ROIs along each suture/synchondrosis. Results: The identification of a definite pattern depended on the suture's type, the closure degree, and the width of the gap (p < 0.001). The interdigitation process was more intricate for most of vault sutures than the skull base sutures/synchondroses. Closing grades 1, 2, and 3 were associated to an identifiable sutural pattern and the cutoff value of 1.45 mm of the gap width allowed to detect an identifiable sutural pattern with the best combination of sensitivity (97%) and specificity (98%). Age and sutural closing degree were inversely related to gap width while positively related to the gap density (p < 0.001). Conclusion: The sutural ossification is an age-related process, distinctive for each suture, and synchondrosis; it occurs neither according to a predefined order along sutural arches nor following a sequential distribution in the cranial fossae, and some sutures continued their growth process during lifetime.